MARITIME STABILITY IN THE STRAIT OF HORMUZ: CHALLENGES, GLOBAL IMPACTS, AND MULTILATERAL DIPLOMACY - Ramadhani, Riva; Marzaman, Atikah (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
The Middle East is a region that has a rich supply of mineral resources. The wealth is with the existence of oil and gas resources which are the center of global energy needs. And the main route to be able to channel these energy needs through the Strait of Hormuz to be able to ensure that oil can be distributed evenly to various countries. This research explores the challenges of maritime stability in the Strait of Hormuz as a strategic global energy distribution route amid geopolitical conflicts in the Middle East region. Using a qualitative method based on descriptive analysis of secondary data from reliable sources, this research identifies the impact of political tensions on global energy security and the surge in world oil prices. The results show that conflicts in the region, including competition between major powers such as the United States and Iran, hamper energy distribution, increase global supply chain risks, and trigger energy inflation. The research highlights the importance of multilateral diplomacy as a solution to ease tensions and maintain maritime stability. And with this condition, it must be ensured that each country in the world conducts multilateral cooperation to be able to turn off global energy security can be achieved amid the high level of geopolitical tension currently occurring in the Middle East Region. Recommendations include strengthening international alliances, diversifying energy pathways and transitioning to renewable energy to reduce dependence on the Strait of Hormuz. The research contribute to a broader understanding of the relationship between geopolitical conflict and global energy security. Major oil-importing countries should start switching to renewable energy such as solar, wind and hydrogen. By doing so, dependence on traditional energy routes, such as the Strait of Hormuz, can be gradually reduced. This diversification of energy sources will also strengthen global energy security in the long run. And it can ensure that international peace can be established by conducting diplomacy between countries to strive for a win-win solution in maintaining energy supply.